Energy Dissipation and Failure Characteristics of Layered Composite Rocks under Impact Load - Wenjie Liu; Ke Yang; Wei Zhen; Xiaolou Chi; Rijie Xu; Xin Lv (Shock and Vibration)
Horizontal layered composite rock samples composed of white and black sandstones with large differences in physical and mechanical properties were tested to explore the dynamic characteristics of layered composite rocks under impact load. Using the split Hopkinson pressure bar test system, the dynamic compression tests of two incident states of stress waves, that is, stress waves from white sandstone to black sandstone (W⟶B) and from black sandstone to white sandstone (B⟶W), were designed and carried out under different impact velocities. Combining the ultrahigh-speed photography system and digital photogrammetry for deformation measurement (DPDM), we obtained the stress wave propagation characteristics, failure characteristics, and particle size distribution characteristics of broken rocks of the composite rocks under the two conditions. The experimental results were compared and analyzed, while stresses and strength conditions at the interface of the composite rock samples were theoretically assessed, yielding the following main findings. The energy dissipation pattern of composite rock had an obvious strain rate effect. The reflected energy and fragmentation energy density of composite rock increased approximately as quadratic functions of the incident energy. Affected by the wave impedance matching relationship, the W⟶B and B⟶W samples were significantly different in terms of the stress wave shape, energy dissipation, average particle size, and fractal dimension of the broken rocks at low impact velocities. However, with an increase in the impact velocities, the two gradually shared the same behavior. When composite rock samples deformed and failed, the macrocracks mostly initiated from the white sandstone. When the crack tip stress of the white sandstone at the interface exceeded the strength of the weakened black sandstone, the crack continued to develop through the two-phase rock interface due to the difference in Poisson’s ratios. The damage degrees and failure modes of the two parts of composite rocks were different: black sandstone was prone to tensile splitting with local shear failure, while white sandstone exhibited shear failure with local tensile splitting. The damage degree of white sandstone exceeded that of black sandstone.